Studi Komparasi Konsep Pendidikan Anak Dalam Islam Menurut Buya Hamka Dan Abdullah Nashih Ulwan - Ahmad Abdur Rokhim; M. Yunus Abu Bakar (Universitas Yudharta Pasuruan, 2021)
This research focuses on the comparative study of Buya Hamka's thoughts with Abdullah Nashih Ulwan regarding the concept of child education in Islam, with a research focus: (1). What is the concept of child education in Islam according to Buya Hamka and Abdullah Nashih Ulwan? (2). What are the differences and similarities in the concept of child education in Islam according to Buya Hamka and Abdullah Nashih Ulwan? This study uses a qualitative approach, with the type of library research. According to Buya Hamka, the goal of children's education in Islam is to make students become servants of God. Meanwhile, Abdullah Nashih Ulwan focuses on the purpose of children's education not only concerned with aspects of intelligence, but more on the dimensions of human quality as a whole with an approach to the piety of students. In terms of methods, Buya Hamka emphasized 4 methods of child education, namely natural methods, habituation training methods, exemplary methods and methods of giving punishment and praise. Abdullah Nashih Ulwan applies child education methods with exemplary, education with habituation (repetition), education with advice, methods of providing training and supervision, education with punishment. The similarity of thoughts of Buya Hamka and Abdullah Nashih Ulwan can be seen from the point of view of children's educational goals that emphasize aspects of spirituality. Meanwhile, in terms of materials and methods of children's education, there are similarities and differences.